Upaya Peningkatan Hasil Belajar Bahasa Indonesia Pada Materi Bermain Di Lingkunganku Untuk Siswa Kelas II SD Negeri 056620 Muka Paya Ujung - Adinda Febrianti Santoso; Eka Farwati; Elpia Suryani (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
The research used is classroom action research (PTK) which aims 1) to determine the process of implementing learning using image media as an effort to improve Indonesian language learning outcomes for class II students at SD Negeri 056620 Muka Paya Ujung; and 2) To determine the increase in Indonesian language learning outcomes through the use of image media in class II students at SD Negeri 056620 Muka Paya Ujung. This classroom action research (PTK) will be carried out at SD Negeri 056620 Muka Paya Ujung. The location of this research was determined based on considerations where it was found that student learning outcomes in Indonesian language subjects were still low. The subjects of this research were class II students at SD Negeri 056620 Muka Paya Ujung in the odd semester of the 2023/2024 academic year, with a total of 8 people (7 male students and 1 female student). This research was carried out in three cycles, each cycle being held in one meeting. Data collection in Classroom Action Research (CAR) takes the form of observations, tests and documentation. Based on the description of the data and discussion of the research results presented, it can be concluded that the learning outcomes of class II students at SD Negeri 056620 Muka Paya Ujung in Indonesian language subjects have generally improved significantly from cycle to cycle by using image media in learning. It can be stated that: 1) Using image media can improve the process of learning Indonesian activities for class II students at SD Negeri 056620 Muka Paya Ujung; and 2) The use of image media in learning can improve Indonesian language learning outcomes for class II students at SD Negeri 056620 Muka Paya Ujung.